2019
DOI: 10.1007/s10803-018-03865-2
|View full text |Cite
|
Sign up to set email alerts
|

Toddler Screening for Autism Spectrum Disorder: A Meta-Analysis of Diagnostic Accuracy

Abstract: Great efforts focus on early detection of autism spectrum disorder, although some scientists and policy-makers have questioned early universal screening. The aim of this meta-analysis was to evaluate the diagnostic accuracy of the different screening tools. Several electronic databases were used to identify published studies. A Bayesian model was used to estimate the screening accuracy. The pooled sensitivity was 0.72 (95% CI 0.61–0.81), and the specificity was 0.98 (95% CI 0.97–0.99). Subgroup analyses to rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 51 publications
(116 reference statements)
1
32
0
2
Order By: Relevance
“…All the other measures did not report any positive or negative predictive values. Overall considered, the measures for which the Sensitivity, Specificity, PPVs and NPVs were reported, demonstrated from moderate to high predictive values (see also [27]), although for the M-CHAT results can be considered more stable compared to other measures that need further and deeper exploration of these properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the other measures did not report any positive or negative predictive values. Overall considered, the measures for which the Sensitivity, Specificity, PPVs and NPVs were reported, demonstrated from moderate to high predictive values (see also [27]), although for the M-CHAT results can be considered more stable compared to other measures that need further and deeper exploration of these properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found these measures promising, none of them can be currently considered as the gold standard in the early detection of risk of ASD and further development in this field is desirable. For example, future studies should improve sensitivity, specificity, NPV, and PPV properties of those measures since they are not considered at all for the FYI and they are barely considered for M-CHAT and Q-CHAT, as also suggested by [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the aforementioned considerations, the FYI and Q-CHAT appear to be promising measures, as indicated in previous studies [ 37 , 38 , 39 ], though several gaps exist in the development of the two measures. Further longitudinal studies are especially needed to test their properties, as also suggested by other authors [ 62 ]. As underlined in a systematic review conducted by Petrocchi et al [ 37 ], the FYI and Q-CHAT cannot yet be considered as the gold standard, which includes instruments with the highest reliability, of the early identification of risk of ASD.…”
Section: Introductionmentioning
confidence: 96%